PENERAPAN MEDIA RODA PUTAR PADA MATERI HAK DAN KEWAJIBAN DI JALAN RAYA DI SDN KARANGREJO 01 - Nisa, Afrila Choirun; Kartinah, Kartinah; Suyoto, Suyoto; Rochajati, Siti (Journal Prakarsa Paedagogia, 2023)
This study aims to determine the application of rotary wheel media to the learning outcomes of class III students at SDN Karangrejo 01 Semarang on the material rights and obligations on the highway. This research uses quantitative methods. The data collection technique in this study was by giving pre-test and post-test questions to class III students. The sample of this research was class III students at SDN Karangrejo 01, totaling 26 students consisting of 10 female students and 16 male students. The results of student learning completeness at the time before the application of the rotary wheel media were 15 students with an average class value of 65.38 then after the application of the rotary wheel media on the material rights and obligations on the highway there was an increase of 7 students with an average class value of 81, 54.